2011
DOI: 10.1089/dia.2010.0233
|View full text |Cite
|
Sign up to set email alerts
|

PIOfix-Study: Effects of Pioglitazone/Metformin Fixed Combination in Comparison with a Combination of Metformin with Glimepiride on Diabetic Dyslipidemia

Abstract: With comparable glycemic control, the fixed PM combination was more efficacious on HDL cholesterol improvement than the GM combination. Additional positive effects were observed for biomarkers of lipid metabolism, β-cell function, activity of the visceral adipose tissue, and chronic systemic inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 26 publications
1
11
0
Order By: Relevance
“…[2122] In patients with type 2 diabetes, there is a strong association between high triglyceride and low HDL cholesterol levels and cardiovascular morbidity and mortality. [22] There have been concerns over liver toxicity with TZDs. [23] In our study, both sitagliptin and pioglitazone caused slight, nonsignificant elevation in mean levels of hepatic enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…[2122] In patients with type 2 diabetes, there is a strong association between high triglyceride and low HDL cholesterol levels and cardiovascular morbidity and mortality. [22] There have been concerns over liver toxicity with TZDs. [23] In our study, both sitagliptin and pioglitazone caused slight, nonsignificant elevation in mean levels of hepatic enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…Although similar improvements in HbA1c were seen with both treatments within 6 months, the pioglitazone + metformin combination had a significantly better effect on triglycerides and HDL cholesterol, and a pronounced hs-CRP improvement was seen in this arm (-0.9 ± 1.9 mg/dl), whereas no effect on hs-CRP could be observed with the glimepiride + metformin combination (0.0 ± 1.8 mg/liter, p < 0.001). 56 Insulin resistance may also be present in normoglycemic individuals, and some of these patients can be diagnosed as having (cardio)metabolic syndrome. Research in these study populations confirmed the efficacy of pioglitazone treatment for reducing chronic systemic inflammation and hs-CRP levels independently from glucose-lowering mechanisms.…”
Section: Effects Of Pioglitazone Treatment On Hs-crp Reductionmentioning
confidence: 99%
“…It has become tremendously popular, and the choice of drug for management of T2DM, owing to its hypoglycemic as well as hypolipidemic effects. The increase in triglycerides in T2DM is accompanied by proatherosclerotic functional changes in HDL and LDL particles [6] and metformin affects a reduction in LDL cholesterol as well as triglyceride levels in blood and hence could be protective against the effects of dyslipidemia [7]. It is the only antidiabetic drug that has been conclusively shown to prevent the cardiovascular complications of diabetes and does not cause weight gain.…”
Section: Introductionmentioning
confidence: 99%